Dietary Fructose Consumption and Triple-Negative Breast Cancer Incidence - Strober, Jordan W.; Brady, Matthew J. (Frontiers in Endocrinology, 2019)
In the past century the western world has found a way to combat most communicative diseases; however, throughout that time the prevalence of obesity, hyperglycemia, and hyperlipidemia have drastically increased. These symptoms characterize metabolic syndrome – a non-communicable disease which has become one of the greatest health hazards of the world. During this same time period the western diet had dramatically changed. Homecooked meals have been replaced by highly-processed, calorically dense foods. This conversion to the current western diet was highlighted by the incorporation of high-fructose corn syrup (HFCS) into sweetened beverages and foods. The consumption of large amounts of dietary sugar, and fructose in particular, has been associated with an altered metabolic state, both systemically and in specific tissues. This altered metabolic state has many profound effects and is associated with many diseases, including diabetes, cardiovascular disease, and even cancer [1]. Specific types of cancer, like triple-negative breast cancer (TNBC), are both responsive to dietary factors and exceptionally difficult to treat, illustrating the possibility for preventative care through dietary intervention in at risk populations. To treat these non-communicable diseases, including obesity, diabetes and cancer, it is imperative to understand systemic and localized metabolic abnormalities that drive its progression. This review will specifically explore the links between increased dietary fructose consumption, development of metabolic disturbances and increased incidence of TNBC.